The Essence of the New Economy - Henning Klodt (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2001)
The New Economy should not be discounted as a temporary stock market phenomenon, but should be recognized as a real and sustainable phenomenon. The basic feature of the transition towards the New Economy is the rising importance of information—both as output and input good—in virtually all sectors of the economy. It would be fallacious to interpret the New Economy as a sector-specific phenomenon. Information increasingly constitutes a crucial input factor both in modern and traditional industries, and the information content of a final output is continuously rising throughout the economy. Present technological change, which is based upon modern information and communications technologies and on biotechnology, measures up to the industrial revolutions of past centuries. It would be premature, however, to identify fundamental trend shifts in aggregate productivity growth, because certain measurement issues are still unsettled and the observation period is still too short. Private firms must develop new business strategies in order to cope with potential market failure resulting from the properties of information goods as public goods, network goods, and experience goods. Bundling and versioning of products, attracting free riders, and —above all— establishing reputation are among the most important business strategies for the New Economy. The New Economy can be expected to reshape the structure of firms and industrial relations. On the one hand, reduced transaction costs will foster small, network-oriented niche suppliers. On the other hand, the New Economy will create substantial firm-size economies of its own—resulting from low marginal costs of information goods and competitive advantages from bundling and the exploitation of reputation. In addition, new types of incentive contracts that can serve to monitor knowledge-intensive activities will gain ground. Since human capital will replace physical capital as the crucial factor of production, improving the qualifications of the labor force is essential to successfully cope with adjustment challenges of the New Economy to the labor market.
Keywords: 330; Lange Wellen; Produktivität; Information; Güter; Informationsmarkt; Marktversagen; Reorganisation; Business Network; Wirtschaftspolitik; Theorie